BUDAYA, STORE ATMOSPHERE DAN KUALITAS PRODUK TERHADAP PERILAKU PEMBELIAN BATIK DI TOKO KAWASAN KAMPUNG BATIK LAWEYAN - Prasetya Ady Purnama; SITI MARYAM; Burhanudin Burhanudin (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2020)
The research aims to find out and describe the influence of simultaneously or partial culture, store atmosphere and product quality to Batik buying behaviour in Batik Store Laweyan Region. This methodology research using quantitative descriptive research. The population was all consumer Batik Store Laweyan Region unknown number. The number of samples was determined with the formula Lemeshow and the result 100 respondents. Sampling method using insidental sampling. The questionnaire used for data retrieval. Data analysis technique used was statistic analysis is multiple linier regression, F test, t test and determination coefficient. This test results the culture, store atmosphere and product quality simultaneously and significance effect on Batik buying behaviour in Batik Store Laweyan Region. culture influential positive and significance effect against the Batik buying behaviour in Batik Store Laweyan Region. Store atmosphere influential positive and significance effect against the Batik buying behaviour in Batik Store Laweyan Region. Product quality influential positive and significance to Batik buying behaviour in Batik Store Laweyan Region The results of the determination of the coefficient indicates culture, store atmosphere and product quality have influence of 57,2% cloth’s buying behaviour in Batik Store Laweyan Region. Suggestion in this research is company should improve the quality of product, espcecially about the characteristics of the product. Companies must be more varied in designing clothes so consumers are interested and purchases by consumers will increase.